2021
DOI: 10.3390/v13122337
|View full text |Cite
|
Sign up to set email alerts
|

Gammaherpesvirus Infections in Cattle in Europe

Abstract: The genus Macavirus, subfamily Gammaherpesvirinae, comprises ungulate viruses that infect domestic and wild ruminants and swine. They cause asymptomatic latent infections in reservoir hosts and malignant catarrhal fever in susceptible species. Lung, spleen, bronchial lymph node, and tongue were collected from 448 cattle (348 necropsied, 100 slaughtered) in Switzerland, United Kingdom, Finland, Belgium, and Germany to determine their infection with bovine herpesvirus-6 (BoHV-6) and gammaherpesviruses of other r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Therefore, tissue samples that had been collected from lung, kidney, and lesioned skin during autopsy were subjected to a quantitative real-time PCR (qPCR) assay for gammaherpesviruses (OvHV2, OvHV1, CpHV2, BoHV6) as described previously. 15,16 We found infection with OvHV2 and very high viral copy numbers in all tested organs (skin: 37,091/100 ng DNA; kidney: 55,961/100 ng DNA; lung: 207,312/100 ng DNA), but did not detect any other gammaherpesvirus.…”
mentioning
confidence: 71%
“…Therefore, tissue samples that had been collected from lung, kidney, and lesioned skin during autopsy were subjected to a quantitative real-time PCR (qPCR) assay for gammaherpesviruses (OvHV2, OvHV1, CpHV2, BoHV6) as described previously. 15,16 We found infection with OvHV2 and very high viral copy numbers in all tested organs (skin: 37,091/100 ng DNA; kidney: 55,961/100 ng DNA; lung: 207,312/100 ng DNA), but did not detect any other gammaherpesvirus.…”
mentioning
confidence: 71%
“…Furthermore, BoGHV6 was associated with lymphoproliferative diseases in buffaloes (Oliveira et al, 2015) and in a cow with pulmonary disease (Headley et al, 2023b) from Brazil. Alternatively, there was no association of BoGHV6 with any disease process in cows from the USA (Collins et al, 2000), in cattle from several European countries (Rosato et al, 2021), as well as from the state of Minas Gerais, Brazil (Oliveira et al, 2015).…”
Section: Bovinementioning
confidence: 97%
“…Experimental studies have confirmed that infections by OvGHV2 in susceptible hosts may occur due to the direct contact with the nasal secretions of asymptomatic sheep [ 12 , 13 , 14 ], demonstrating that this is most the important epidemiological form of transmission. Nevertheless, transplacental infection of OvGHV2 was confirmed between an infected cow and a fetus [ 15 ], and infection via artificial insemination was suspected on a commercial pig farm [ 16 ], while OvGHV2 was identified in fetal tissues of cattle [ 17 , 18 ] and in the male reproductive system of sheep [ 19 ]. Collectively, these findings suggest the occurrence of vertical infection due to OvGHV2.…”
Section: Introductionmentioning
confidence: 99%